2020
DOI: 10.3390/nano10020378
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sphere Template Derived Hollow Nanostructure for Photocatalysis and Gas Sensing

Abstract: As a green and preferred technology for energy crisis and environmental issues, continuous research on photocatalysis and gas sensing has come forth at an explosive rate. Thus far, promising synthetic methods have enabled various designs and preparations of semiconductor-based nanostructure which have shown superior activity. This review summarized various synthetic routines toward carbon sphere template derived hollow nanostructures and their successful attempts in synthesize doping, solid solution, heterostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Although silica is the most commonly used hard template, other materials—such as inorganic salts or oxides (e.g., NaCl, KCl, MgO, CaCO 3 ) [ 85 ], carbon spheres [ 86 ], and organic polymer spheres [ 87 , 88 ]—can also effectively play this role. One interesting example of a hard template is rubidium chloride [ 52 ], which can be mixed with PA to afford aggregated, spherical carbon particles (<30 μm) after annealing at 800 °C.…”
Section: Methods For Synthesizing Heteroatom-doped Carbon Materialsmentioning
confidence: 99%
“…Although silica is the most commonly used hard template, other materials—such as inorganic salts or oxides (e.g., NaCl, KCl, MgO, CaCO 3 ) [ 85 ], carbon spheres [ 86 ], and organic polymer spheres [ 87 , 88 ]—can also effectively play this role. One interesting example of a hard template is rubidium chloride [ 52 ], which can be mixed with PA to afford aggregated, spherical carbon particles (<30 μm) after annealing at 800 °C.…”
Section: Methods For Synthesizing Heteroatom-doped Carbon Materialsmentioning
confidence: 99%
“…Synthesis of Carbon@Titania Yolk-Shell Nanostructures: Carbon spheres were prepared by hydrothermal process. [27][28][29] Glucose (C 6 H 12 O 6 , 99.5%, Sigma Aldrich) was first dissolved in deionized water and stirred. The transparent glucose solution was heated to 200 °C at a heating rate of 10 °C min −1 and further maintained for 4 h. The black powder obtained was washed and centrifuged with deionized water and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, hollow structures having a bowl-like shape would provide more adsorption or reaction sites for bioactive molecules to get encapsulated at lower densities . However, most of the studies reported on the formation of hollow structures entirely depended on template-based approaches, which were more tedious, time-consuming, and non-environmentally friendly. , Hence, it would be worthwhile to resort to alternate methods such as polymeric self-assembly as a simplistic strategy to prepare hollow structures such as bowl-shaped nano/microparticles to overcome the aforesaid drawbacks. , Additionally, the formation of bowl-shaped structures from biocompatible molecules like amino acids or peptides can be further beneficial in the field of drug delivery. Following this, a recently published study by our group represented a new microfluidic-based flow fabrication method to form self-assembled single amino acid (Fmoc-Cys­(Trt)-OH)-based nanobowls (NBs).…”
Section: Introductionmentioning
confidence: 99%
“…7 However, most of the studies reported on the formation of hollow structures entirely depended on templatebased approaches, which were more tedious, time-consuming, and non-environmentally friendly. 8,9 Hence, it would be worthwhile to resort to alternate methods such as polymeric self-assembly as a simplistic strategy to prepare hollow structures such as bowl-shaped nano/microparticles to overcome the aforesaid drawbacks. 10,11 Additionally, the formation of bowl-shaped structures from biocompatible molecules like amino acids or peptides can be further beneficial in the field of drug delivery.…”
Section: ■ Introductionmentioning
confidence: 99%